'Divus Iulius Caesar': constructions around Julius Caesar in Velleius, Plutarch and Suetonius - José, Natália Frazão (Romanitas - Revista de Estudos Grecolatinos, 2013)
Numerous are the analyzes of Gaius Julius Caesar, an important Roman who lived in the first century BC. Several authors, from different periods, devoted themselves to narrate the life of this personage, his accomplishments, his achievements, his victories and defeats. So, we have countless faces of Caesar, multiple constructs that have varied meanings, diverse goals. It is with this in mind that we propose, at this time, to analyze how three authors, Velleius, Plutarch and Suetonius, belonging to the chronological arc of Roman Principate, depicting the life of Julius Caesar, highlighting the differences and similarities between these accounts.
Keywords: Rome; Julius Caesar; Velleius; Plutarch; Suetonius